Personal and Social Competencies as Drivers of Entrepreneurial Success in Malaysia’s SME Sector - Munap, Rudzi Binti; Nwadiuto, Obeto Mercy; Malik, Ikmal Abdul (International Review of Management and Marketing, 2026)
This study examines the influence of social and personal skills on entrepreneurial success among small and medium-sized enterprises (SMEs) in Malaysia. Entrepreneurs must develop expertise, enhance interpersonal competencies, and safeguard business success to thrive in competitive environments. Interaction with other business owners fosters idea generation and strategic development. Using purposive sampling, data were collected from 142 entrepreneurs via a structured online questionnaire. The data were analysed using SPSS and partial least squares structural equation modelling (PLS-SEM). Results reveal a significant positive relationship between both social and personal skills and entrepreneurial success. Social interaction with other business owners fosters idea generation, strategic thinking, and relationship-building, which are essential for business sustainability and growth. The findings also underscore the importance of digital entrepreneurship in cultivating soft skills essential for business sustainability. The study contributes both practically and empirically to the body of knowledge by highlighting the importance of interpersonal competencies and privacy management in enhancing entrepreneurial outcomes.